Media exposure and tobacco product addiction beliefs: Findings from the 2015 Health Information National Trends Survey (HINTS–FDA 2015). (September 2017) - Donaldson, Elisabeth A.; Hoffman, Allison C.; Zandberg, Izabella; Blake, Kelly D.
Abstract: Background: Addiction beliefs about tobacco use are associated with intentions to use and use of tobacco products. Exposure to information about tobacco products in media sources may affect addiction beliefs. Purpose: To examine the relationship between media exposure and tobacco product addiction beliefs. Methods: A nationally representative sample of US adults (n = 3738) from the 2015 National Cancer Institute's Health Information National Trends Survey was used to examine addiction beliefs about cigarettes, cigars, smokeless tobacco, electronic cigarettes, hookah/waterpipe tobacco, and roll-your-own cigarettes. We used logistic regression to examine the relationship between media exposure and addiction beliefs. We defined media exposure by hours exposed, as well as exposure to tobacco use health effects information through media sources including social media. We categorized media sources by whether respondents actively or passively engaged with the source. Findings: A majority (60.6% to 87.3%) of respondents believed that cigarettes, cigars, roll-your-own cigarettes and smokeless tobacco are addictive. Less than half of respondents believed that electronic cigarettes or hookah/waterpipes are addictive (45.2% and 49.8%, respectively). Respondents exposed to messages about tobacco use health effects on active media channels (e.g., social media) had greater odds of believing that smokeless tobacco (adjusted odds ratio [AOR] = 1.48), hookah/waterpipe (AOR = 1.69), and roll-your-own cigarettes (AOR = 1.61) are addictive. Respondents exposed to tobacco use health effects messages on passive media channels (e.g., television), had greater odds of believing that cigarettes (AOR = 2.76) and electronic cigarettes (AOR = 2.12) are addictive. Conclusions: US adult exposure to information about the health effects of tobacco use was associated with addiction beliefs about tobacco products. Highlights: Most US adults believe that cigarettes, cigars, roll-your-own cigarettes, and smokeless tobacco are addictive. Less than half of US adults believe that e-cigarettes and hookah/waterpipe are addictive. Exposure to messages about the health effects of tobacco use was associated with addiction beliefs.